Psycholinguistic screening test for Tamil children with reading difficulties in Sri Lanka - Naina Mohamed Safeek (Educational Futures, 2025)
Reading development forms the cornerstone of every child’s educational journey, yet not all naturally acquire proficient reading skills, necessitating early identification and intervention. Sri Lanka currently lacks a comprehensive national programme to address reading difficulties. This study aims to create and validate a Psycholinguistic Screening Test (PST) tailored for Grade 6 (junior secondary) Tamil-speaking students (N=78) in Sri Lanka who struggle with reading. Grounded in the Simple View of Reading (SVR), the PST evaluates crucial dimensions of reading proficiency, including phonological awareness, sound-symbol association, syllable knowledge, word morphology, word syntax, semantic skills, and reading comprehension. The PST demonstrates robust face and content validity, with an I-FVI score of 0.88 and I-CVI scores of 0.89 for all items among all raters, confirming its validity. Test-retest reliability analysis indicates improved scores from pre-test (M=33.0, SD=14.5) to post-test (M=39.1, SD=14.5), with a strong positive correlation (r = 0.919, p < .01, 2-tailed) between the measures. Overall, the PST exhibits promising validity and reliability. Its development and validation offer significant potential for addressing reading difficulties among Grade 6 Tamil-speaking students in Sri Lanka. Practical implications encompass early identification and intervention strategies, tailored instruction methods, increased awareness, inclusive educational practices, research avenues, multilingual adaptation, policy implementation, parental involvement, and longitudinal studies.